2005
DOI: 10.1159/000085661
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Relapse after Therapy with Curative Intention: A Diagnostic and Therapeutic Dilemma

Abstract: Prostate cancer is the most common malignant disease and second in causes of cancer death among men in Western Europe and North America. Despite improved surgical and irradiation techniques tumor relapse after curatively intended therapy is not uncommon. Due to the difficulty in discriminating local and systemic progression, it is often difficult to decide what this means for the patient and what kind of second-line treatment has to be given. Modern imaging techniques (MRI with endorectal coil, Choline-PET-CT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…Prostate cancer is one of the most prevalent male cancers in Germany and other developed countries, with an estimated annual incidence of 678,000 new cases worldwide [5]. Standard therapy includes radical prostatectomy and radiotherapy [6]. Remarkably, given the high incidence, studies on symptom distress and its impact on emotional well-being of patients have been relatively rare so far in comparison to research on other cancer types such as breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer is one of the most prevalent male cancers in Germany and other developed countries, with an estimated annual incidence of 678,000 new cases worldwide [5]. Standard therapy includes radical prostatectomy and radiotherapy [6]. Remarkably, given the high incidence, studies on symptom distress and its impact on emotional well-being of patients have been relatively rare so far in comparison to research on other cancer types such as breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…RecentstudieshavedemonstratedthataserumPSAlevel ofgreaterthan100ng/mlyieldeda50-100%positivepredic-tivevalueforbonemetastasis [8][9][10][11].Toourknowledge,the …”
Section: Conflict Of Interestmentioning
confidence: 98%
“…shown that, for groups of men with prostate cancer, serum PSAcorrelatesdirectlywithadvancedclinicalandpathologicalstage [8,9]. RecentstudieshavedemonstratedthataserumPSAlevel ofgreaterthan100ng/mlyieldeda50-100%positivepredic-tivevalueforbonemetastasis [8][9][10][11].Toourknowledge,the …”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Помимо хирургического лечения у больных с прогрессированием РПЖ и единичными метастазами в ЛУ в настоящее время широко изучает-ся другой терапевтический подход. Как известно, ЛТ активно используют в лечении пациентов с РПЖ [32][33][34][35][36][37][38][39][40][41]. В последнее время все чаще применяют стерео-таксическую ЛТ.…”
Section: диагностика и лечение опухолей мочеполовой системы рак предunclassified